Error analysis in solving mathematical communication problem of junior high school students - R A Prafianti; D Dasari; A Jupri (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research was a descriptive qualitative research. This research aims to analyze students’ error in solving mathematical communication problem on circle topic. Population in this research was all students studying in the 9th grade of SMP Negeri 3 Lembang Bandung Jawa Barat. The sample was 39 students (22 female and 17 male) that was chosen by purposive sampling technique. Data was collected from students through essay test. The data was analyzed with descriptive way. The results of this research indicate that percentage of error in using circle area formula was 5.1%, error in linking concept is 25.6%, and error in understanding the meaning of the problem was 17.9%. Students’ error in solving mathematical communication problem was caused by many factors, such as students were not used to solve mathematical communication problem, less accuracy, and less conceptual understanding of mathematics. Based on the result, the researcher suggest to: 1) increase students’ understanding of formula rather than memorize it, 2) increase students’ understanding of problem, and 3) give students more exercise related non-routine problem.